A Nanomicellar Prodrug Carrier Based on Ibuprofen-Conjugated Polymer for Co-delivery of Doxorubicin - Li, Zuojun; Sun, Jingjing; Huang, Yixian; Liu, Yanhua; Xu, Jieni; Chen, Yichao; Liang, Lei; Li, Jiang; Liao, Qiongfeng; Li, Song; Zhou, Kechao (Frontiers in Pharmacology, 2018)
Ibuprofen (IBU) is a nonsteroidal anti-inflammatory drug (NSAID), which is widely used to reduce fever, treat inflammation and acute pain. Recently, its application in cancer treatment is also being explored. In this work, we synthesized a well-defined IBU-based amphiphilic diblock copolymer via reversible addition fragmentation transfer (RAFT) polymerization of IBU-based vinyl monomer. The amphiphilic copolymer POEG-b-PVBIBU (denoted as POVI) was composed of a hydrophilic poly(oligo(ethylene glycol) block and a hydrophobic IBU-bearing prodrug block, which was able to self-assemble into prodrug nanomicelles. In addition, it could serve as a carrier to co-load other drugs including doxorubicin (DOX), paclitaxel (PTX) and docetaxel (DTX). By using DOX as a model anti-cancer drug, the delivery function of POVI carrier, including the drug release, in vitro cytotoxicity, cellular uptake and in vivo anti-tumor activity, was evaluated. DOX-loaded POVI micelles exhibited high stability and sustained release of DOX. Besides, DOX/POVI micelles were effectively taken up by tumor cells with an efficiency comparable to that of free DOX. Moreover, in vivo studies showed that POVI carrier itself had modest anti-tumor activity. After loading DOX, the anti-tumor activity was significantly increased, which was significantly higher than that of free DOX. Our results suggest POVI polymer represents a simple and effective dual-functional carrier for co-delivery of IBU and DOX to improve the anticancer activity.